Pharmacokinetics and bioequivalence assessment of two prucalopride formulations in healthy Chinese women: a randomized, open-label, two-period, two-sequence, self-crossover study - Huang, Xiangxin; Wang, Ying; Li, Bei; Shen, Xiaoqun; Tao, Xuexia; Zheng, Wenwen; Luo, Qi; Xiong, Lei; Wang, Lin; Cai, Shufan (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the pharmacokinetic (PK) bioequivalence of generic and branded prucalopride formulations.MethodsTwenty-four healthy female subjects were enrolled in both fasted and fed trials, with each subject receiving either the test (generic) or reference (branded) formulation after an overnight fast. Blood samples were collected up to 72 h post-administration. Plasma concentrations of prucalopride were quantified using ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS), and the corresponding PK parameters were subsequently calculated. Clinical safety data were monitored throughout the trial period.ResultsAll 24 subjects completed both the fasted and fed trials. No significant differences were found in the PK data between the test and reference formulations for either the fasted or fed states. The Wilcoxon signed-rank test of Tmax revealed no significant differences between the two formulations in both the fasted (P = 0.319) and fed (P = 0.973) states. The 90% confidence intervals (CIs) for the bioequivalence parameters fell within the 80%–125% range, which meets the standard bioequivalence acceptance criteria. Additionally, there were no significant differences in the incidence of adverse events (AEs) between the generic and branded formulations, and no serious AEs were reported throughout the trial period.ConclusionThe generic and branded prucalopride tablets were bioequivalent in terms of PK parameters and demonstrated no clinically relevant differences in safety outcomes.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/clinicaltrials.prosearch.dhtml, identifier CTR20232669.